THE CORRELATION BETWEEN MOTHERS' KNOWLEDGE LEVEL AND HANDLING TEMPER TANTRUM IN PRESCHOOL CHILDREN (4-6 YEARS): MOTHERS' KNOWLEDGE LEVEL; HANDLING TEMPER TANTRUM;CORRELATION BETWEEN MOTHERS' KNOWLEDGE LEVEL AND HANDLING TEMPER TANTRUM IN PRESCHOOL CHILDREN (4-6 YEARS) - Asiah (Jurnal Kesehatan Ilmiah Aufa Royhan, 2025)
Temper tantrums are a common emotional developmental problem in preschool-age children caused by unfulfilled desires so that children throw tantrums, cry, and throw things. Many mothers do not know how to handle temper tantrums properly. This study aims to determine the relationship between mothers' knowledge levels and temper tantrum management in preschool-aged children (4-6 years) at TK RA Istiqomah, Bongas Wetan Village, Sumberjaya Subdistrict, Majalengka Regency, in 2024. This study employed a quantitative method with a correlational research design. The population included all mothers whose children attended TK RA Istiqomah, totaling 54 individuals. The sample consisted of 52 mothers selected using total sampling. Statistical data analysis was conducted using the Chi-Square test at a significance level of 5% (0.05). The results showed that 22 mothers (42.3%) had a moderate level of knowledge, and 19 mothers (36.5%) demonstrated a moderate level of temper tantrum management. The Chi-Square test yielded a p-value of 0.002 (p < 0.05), indicating a significant relationship between mothers' knowledge levels and temper tantrum management. This study encourages mothers to improve their knowledge of handling and understanding their children's temper tantrums by participating in parenting activities organized by TK RA Istiqomah.